Synthesis and Diacylglycerol Acyltransferase‐1 Inhibition of Azabicyclo[3.1.0]hexane Derivatives. (June 2015) - Han, Seo‐Jung; Lee, Gwi Bin; Kwak, Hyun Jung; Pagire, Suvarna H.; Kim, Ji Young; Pagire, Haushabhau S.; Park, Sung Bum; Chae, Chong Hak; Lee, Joo Yun; Kim, Ki Young; Rhee, Sang Dal; Kim, Hee Youn; et al.
<x xml:space="preserve">Abstract</x>